Dinamika Regulasi Penyadapan dalam Undang-Undang dan Putusan Mahkamah Konstitusi - Ramadhan, Tutik Nurul; Bambang Sugiri; Yuliati (Universitas Airlangga, 2022)
AbstractThe regulation of wiretapping in Indonesia still contains many problems, such as provisions regarding wiretapping which are scattered in various laws and regulations. One example and its consequence is the decision of the Constitutional Court 70/PUU-XVII/2019 which annuls the provision regarding the requirement for a permit to the KPK supervisory board. This study aims to describe and analyze the dynamics of wiretapping arrangements in laws and decisions of the Constitutional Court. This study uses a normative juridical research method with a statutory approach and case studies in court decisions. The results show that in Indonesia there are no standard provisions regarding wiretapping procedures, all provisions in special crimes regulate wiretapping materials with different procedures and standards. The Constitutional Court's constitutional considerations state that wiretapping is part of the criminal justice system which is a criminal procedural law regime that limits human rights, so it must have regulatory legal certainty and must also be specifically regulated in the provisions of the law. Keywords: Regulations; Wiretapping; Laws; Constitutional Court Decisions. AbstrakPengaturan penyadapan di Indonesia masih banyak mengandung permasalahan, seperti ketentuan mengenai penyadapan yang tersebar diberbagai peraturan perundang-undangan. Salah satu contoh dan akibatnya adalah putusan MK 70/PUU-XVII/2019 yang membatalkan ketentuan tentang keharusan izin kepada dewan pengawas KPK. Penelitian ini bertujuan untuk menguraikan dan menganalisis dinamika pengaturan penyadapan dalam undang-undang dan putusan MK. Riset ini mempergunakan metode riset yuridis normatif yang berpendekatan perudang-undangan serta studi kasus dalam putusan pengadilan. Hasil riset menampilkan bahwasanya tidak di Indonesia tidak ada ketentuan baku mengenai prosedur penyadapan, seluruh ketentuan dalam tindak pidana khusus mengatur materi penyadapan dengan prosedur dan standart yang berbeda-beda. Pertimbangan konstitusional MK menyatakan bahwa penyadapan adalah bagian dari sistem peradilan pidana yang merupakan rezim hukum acara pidana yang membatasi hak asasi manusia, sehingga harus memiliki kepastian hukum regulasi dan juga harus diatur secara spesifik dalam ketentuan undang-undang. Kata Kunci: Regulasi; Penyadapan; Undang-Undang; Putusan MK.